The effects of divorce parents on child's behavior / Saidatul Aziera Mohd Shariff ... [et al.] - Mohd Shariff, Saidatul Aziera; Ridzuan, Abdul Rauf; Hamzah, Mohd Hilmi; Sultan Mohideen, Rosilawati; Ilyas, Ilya Yasnoriza (Faculty of Communication & Media Studies, 2021)
This study is done in order to study the effects of divorce parents on child's behaviour. A divorce happens after husband and wife decide not to live together anymore and they no longer want to be married to each other. This study used a systematic literature review that combined all study's findings. The effects of divorce parents to children can be both either positive or negative. A total of 1000 articles seemed to correspond to the criteria according to the titles and abstracts. Two articles that studied in Malaysian fulfilled the criteria, (Morin, 2019) and (Garoo, 2019). A final total of 20 articles were selected for this systematic literature review, but only 10 which were found and picked for this topic. The effects of divorce upon child such as peer relations, stress, aggression, work effectiveness at school were happened. Moreover, in many cases, teenage children even drop out of school and get into drugs.